Cover Picture: A High Contrast Tri‐state Fluorescent Switch: Properties and Applications (Chem. Asian J. 22/2016). Issue 22 (18th November 2016) - Su, Xing; Wang, Yi; Fang, Xiaofeng; Zhang, Yu‐Mo; Zhang, Ting; Li, Minjie; Liu, Yifei; Lin, Tingting; Zhang, Sean Xiao‐An
Abstract : A fluorescent molecular switch with both high‐contrast cyan/orange‐colored states (Δ λ =120 nm) and an off state ( Φ F <0.01%) has been prepared by fusing an aggregation‐induced emissive tetraphenylethene with a molecular switch of spiropyran. Reversible switching between any two of the three states has been achieved by tuning both the molecular structure and their packing modes in the solid state with different external stimuli, which makes it very promising in fluorescent display, chemical/mechanical sensing, and anti‐counterfeiting applications.. More information can be found in the Full Paper by Yifei Liu, Tingting Lin et al. onpage 3205 in Issue 22, 2016 (DOI:10.1002/asia.201601096 ).